Methoden zur Modellierung und Analyse von Geschäftsprozessen zur Unterstützung des Business Process Reengineering - Fahrwinkel, Uta

Beschreibung von Datenaustausch eines verteilten Fertigungssteuerungssystems - Ketterer, Norbert

Spezifikation und Klassifikation von Methoden zur Definition hierarchischer Abläufe - Hartmann, Thomas

Die Szenario-Technik - Werkzeug für den Umgang mit einer multiplen Zukunft - Gausemeier, Jürgen

Methodische Anforderungsverarbeitung auf Basis eines objektorientierten Anforderungsmodells - Humpert, Axel

Kommentar § 5 c GWB (Einkaufskooperationen) - Krimphove, Dieter (Gesetz gegen Wettbewerbsbeschränkungen und Europäisches Kartellrecht)

Systematik in der Flachgetriebeentwicklung - Zimmer, Detmar (TECHNICA - Illustrierte technische Zeitschrift)

Flachgetriebe: Ausführungen, Antriebsvarianten und Einsatzgebiete. Flexibilität im Sinn - Zenker, Dieter; Zimmer, Detmar (KEM - Konstruktion Elektronik Maschinenbau)

Generationswechsel. Überarbeitung einer Getriebebaureihe - Zimmer, Detmar (Der Konstrukteur - Magazin für Konstruktion und Entwicklung)

Direct Algebraic Reconstruction in Electromagnetic Flow Tomography - Trächtler, Ansgar; Wernsdörfer, Andreas (Frontiers in Industrial Process Tomography, Engineering Foundation)

Stress Tensor Tomography Using Integrated Photoelasticity - Trächtler, Ansgar (Frontiers in Industrial Process Tomography, Engineering Foundation)

Intelligent visualization systems in educational environments - Kienegger-Domik, Gitta (Proceedings of ED-MEDIA `95)

Routing with Bounded Buffers and Hot-Potato Routing in Vertex-Symmetric Networks - Meyer auf der Heide, Friedhelm; Scheideler, Christian (ESA)

Space-Efficient Routing in Vertex-Symmetric Networks (Extended Abstract) - Meyer auf der Heide, Friedhelm; Scheideler, Christian (SPAA)

Exploiting Storage Redundancy to Speed Up Randomized Shared Memory Simulations - Meyer auf der Heide, Friedhelm; Scheideler, Christian; Stemann, Volker (STACS)

Attributed Graph Transformations with Controlled Application of Rules - Heckel, Reiko; Müller, Jürgen; Taentzer, Gabriele; Wagner, Annika (Proceedings of the Colloquium on Graph Transformation and its Application in Computer Science)
We present a combination of recent extensions to single-pushout graph transformations, as there are attribution, application conditions and amalgamated graph transformations and add a simple transaction concept on top of this formalism. Thereby, we provide the formal basis for several examples, where these concepts are used in combination.

Record Linkage of Anonymous Data by Control Numbers - Thoben, Wilfried; Appelrath, Hans-Jürgen; Sauer, Stefan (Proceedings of the 18th Annual Conference of the Gesellschaft für Klassifikation, Oldenburg (Germany))

Embedding of Conditional Graph Transformations - Heckel, Reiko (Proceedings of the Colloquium on Graph Transformation and its Application in Computer Science)
Single pushout graph transformations at injective matches are extended by negative application conditions. It is shown, how right-sided application conditions can be transformed into equivalent left-sided ones. Based on this result, conditional derived rules are introduced and a theorem, similiar to the double pushout embedding theorem is shown. Finally, three variants of contextual application conditions are discussed with respect to their expressive power and expected results.

Planung und Durchführung der Ausbildung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis, Ausbilden im Handwerk. Dozentenhandbuch für Teil IV der Meisterausbildung.)

Grundfragen der Berufsbildung - Euler, D.; Kremer, H.-Hugo; Theis, M. (Meisterprüfung - Lernen für die Praxis, Ausbilden im Handwerk. Dozentenhandbuch für Teil IV der Meisterausbildung.)

Grundfragen der Berufsbildung - Euler, D.; Kremer, H.-Hugo; Theis, M. (Meisterprüfung - Lernen für die Praxis, Ausbilden im Handwerk)

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Solar Electricity up to 30% less expensive by optical and thermal enhanced PV modules - Krauter, Stefan (Proceedings of the ISES Solar World Congress 1995, Harare (Simbabwe), 11.–15. September 1995.)

STOPV: A Development Tool for Thermal and Optical Optimization of PV Module Encapsulations - Onneken, K.; Krauter, Stefan (Proceedings of the 1995 ISES Solar World Congress, Harare (Simbabwe), 11.–15. September 1995)

Actual Optical and Thermal Performance of PV-Modules - Krauter, Stefan (Proceedings of the ISES Solar World Congress 1995, Harare (Simbabwe), 11.–15. September 1995)

Thermal and Optical Enhanced PV-Modules - Krauter, Stefan (Proceedings of the 13th European Photovoltaic Solar Energy Conference, Nizza (Frankreich), 23.–27. Oktober 1995, S. 2306–2309.)

Graphische Spezifikation ausgewählter Teile von AGG - einem algebraischen Graphgrammatiksystem - Conrad, Mirko; Gajewsky, Magdalena; Holl-Biniasz, Rainer; Rudolf, Michael; Demuth, Jochen; Weber, Stephan; Heckel, Reiko; Müller, Jürgen; Taentzer, Gabriele; Wagner, Annika

Specialization of Object Life Cycle Definitions - Ebert, Jürgen; Engels, Gregor
Several object-oriented modeling approaches propose to describe the dynamic behaviour of objects by state transition diagrams. None of them provides precise rules or conditions for the interrelation between the behaviour description of classes and those of their subclasses. In this paper, we discuss this interrelation in detail. It turns out that one has to distinguish between the observable and the invocable behaviour of objects and that different compatibility requirements between the diagrams exist depending on the type of behaviour.

Encapsulated Hierarchical Graphs, Graph Types, and Meta Types - Engels, Gregor; Schürr, Andy

Coordination by Behavioural Views and Communication Patterns - Groenewegen, Luuk; Engels, Gregor (Proceedings of the 4th European Workshop on Software Process Technology (EWSPT 1995), Noordwijkerhout (The Netherlands))

A Compositional Approach to Structuring and Refinement of Typed Graph Grammars - Corradini, Andrea; Heckel, Reiko (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Based on a categorical semantics that has been developed for typed graph grammars we uses colimits (pushouts) to model composition and (reverse) graph grammar morphisms to describe refinements of typed graph grammars. Composition of graph grammars w.r.t. common subgrammars is shown to be compatible with the semantics, i.e. the semantics of the composed grammar is obtained as the composition of the semantics of the component grammars. Moreover, the structure of a composed grammar is preserved during a refinement step in the sense that compatible refinements of the components induce a refinement of the composition. The concepts and results are illustrated by an example.

GRAPHIT: Graphical Support and Integration of Formal and Semiformal Methods for Software Specification and Development - Bardohl, Bernhard; Bardohl, Roswitha; Castro, Paulo; Ehrig, Hartmut; Heckel, Reiko; Ribeiro, Leila; Nunes, Daltro; Martini, Alfio (Proceedings of the 3rd German-Brazilian Workshop on Information Technology (1995), Berlin (Germany))
The overall aim of this paper is a proposal how to bridge the gap between formal specification techniques developed in research projects and semi--formal or informal specifications used in industrial practice. The main idea to overcome these problems is to develop graphical support for formal methods in order to increase acceptance by practitioners and to provide means for integration of formal and semi--formal methods. More specifically suitable concepts will be developed to combine algebraic specifications, Petri Nets, and Graph Grammars with each other and with distinguished graphical components to be used by industrial partners.

Encapsulated Hierarchical Graphs, Graph Types, and Meta Types - Engels, Gregor; Schürr, Andy (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Currently existing graph grammar-based specification languages have serious problems with supporting any kind of “specification-in-the-large” activities. More precisely, they have deficiencies with respect to modeling hierarchical data structures or specifying meta activities like manipulation of graph schemata. Furthermore, already proposed graph grammar module concepts are still too abstract to be useful in practice. Our contribution addresses these problems by introducing a new hierarchical graph data model with an infinite number of schema, meta-schema, etc. layers. It forms the base for a forthcoming concrete modular graph grammar specification language where in addition information hiding aspects like explicit export and import interfaces are expressible.

Ensuring Consistency of Conditional Graph Grammars - A constructive Approach - Heckel, Reiko; Wagner, Annika (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Symmetry Breaking Bifurcations of Chaotic Attractors - Aston, Philip J.; Dellnitz, Michael (International Journal of Bifurcation and Chaos)
In an array of coupled oscillators, synchronous chaos may occur in the sense that all the oscillators behave identically although the corresponding motion is chaotic. When a parameter is varied this fully symmetric dynamical state can lose its stability, and the main purpose of this paper is to investigate which type of dynamical behavior is expected to be observed once the loss of stability has occurred. The essential tool is a classification of Lyapunov exponents based on the symmetry of the underlying problem. This classification is crucial in the derivation of the analytical results but it also allows an efficient computation of the dominant Lyapunov exponent associated with each symmetry type. We show how these dominant exponents determine the stability of invariant sets possessing various instantaneous symmetries, and this leads to the idea of symmetry breaking bifurcations of chaotic attractors. Finally, the results and ideas are illustrated for several systems of coupled oscillators.

Admissible symmetry increasing bifurcations - Dellnitz, M; Heinrich, C (Nonlinearity)

A note on the shadowing lemma and symmetric periodic points - Dellnitz, M; Melbourne, I (Nonlinearity)

Cycling Chaos - Dellnitz, Michael; Field, Michael; Golubitsky, Martin; Ma, Jun; Hohmann, Andreas (International Journal of Bifurcation and Chaos)

Spirals in Scalar Reaction–Diffusion Equations - Dellnitz, Michael; Golubitsky, Martin; Hohmann, Andreas; Stewart, Ian (International Journal of Bifurcation and Chaos)
Spiral patterns have been observed experimentally, numerically, and theoretically in a variety of systems. It is often believed that these spiral wave patterns can occur only in systems of reaction–diffusion equations. We show, both theoretically (using Hopf bifurcation techniques) and numerically (using both direct simulation and continuation of rotating waves) that spiral wave patterns can appear in a single reaction–diffusion equation [ in u(x, t)] on a disk, if one assumes "spiral" boundary conditions (u r = mu θ ). Spiral boundary conditions are motivated by assuming that a solution is infinitesimally an Archimedian spiral near the boundary. It follows from a bifurcation analysis that for this form of spirals there are no singularities in the spiral pattern (technically there is no spiral tip) and that at bifurcation there is a steep gradient between the "red" and "blue" arms of the spiral.

Transforming comparison model lower bounds to the parallel-random-access-machine - Breslauer, Dany; Czumaj, Artur; Dubhashi, Devdatt P.; Meyer auf der Heide, Friedhelm (Information Processing Letters)

The constrained Liapunov-Schmidt procedure and periodic orbits - Golubitsky, Martin; Marsden, Jerrold; Stewart, Ian; Dellnitz, Michael (Normal Forms and Homoclinic Chaos)

A packet routing protocol for arbitrary networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (STACS 95)

Shared memory simulations with triple-logarithmic delay - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Lecture Notes in Computer Science)

Optimal trade-offs between size and slowdown for universal parallel networks - Meyer auf der Heide, Friedhelm; Storch, Martin; Wanka, Rolf (Proceedings of the seventh annual ACM symposium on Parallel algorithms and architectures - SPAA '95)

Improved optimal shared memory simulations, and the power of reconfiguration - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Proceedings Third Israel Symposium on the Theory of Computing and Systems)

Hot-potato routing on multi-dimensional tori - Meyer auf der Heide, Friedhelm; Westermann, Matthias (Graph-Theoretic Concepts in Computer Science)

Truly efficient parallel algorithms: c-optimal multisearch for an extension of the BSP model - Bäumker, Armin; Dittrich, Wolfgang; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Exploiting Parallelism in Constraint Satisfaction for Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (J.UCS Journal of Universal Computer Science)

Application of Clustering Techniques to Mixture Density Modelling for Continuous-Speech Recognition - Dugast, Christian; Beyerlein, Peter; Haeb-Umbach, Reinhold (ICASSP, Detroit)
Clustering techniques have been integrated at different levels into the training procedure of a continuous-density hidden Markov model (HMM) speech recognizer. These clustering techniques can be used in two ways. First acoustically similar states are tied together. It will help to reduce the number of parameters but also allow to train otherwise rarely seen states together with more robust ones (state-tying). Secondly densities are clustered across states, this reduces the number of densities while at the same time keeping the best performances of our recognizer (density-clustering). We have applied these techniques both to word-based small-vocabulary and phoneme-based large-vocabulary recognition tasks. On the WSJ task, we could achieve a reduction of the word error rate by 7%. On the TI/NIST-connected digit task, the number of parameters was reduced by a factor 2-3 while keeping the same string error rate.

User interface design of voice controlled consumer electronics - Gamm, Stephan; Haeb-Umbach, Reinhold (Philips Journal of Research)
Today speech recognition of a small vocabulary can be realized so cost-effectively that the technology can penetrate into consumer electronics. But, as first applications that failed on the market show, it is by no means obvious how to incorporate voice control in a user interface. This paper addresses the issue of how to design a voice control so that the user perceives it as a benefit. User interface guidelines that are adapted or specific to voice control are presented. Then the process of designing a voice control in the user-centred approach is described. By means of two examples, the car stereo and telephone answering machine, it is shown how this is turned into practice.

Human Factors of a Voice-Controlled Car Stereo - Gamm, Stephan; Haeb-Umbach, Reinhold (Eurospeech, Madrid)

The Usability Engineering of a Voice-Controlled Answering Machine - Gamm, Stephan; Haeb-Umbach, Reinhold; Langmann, Det (International Symposium on Human Factors in Telecommunications, Melbourne)

Speech recognition algorithms for voice control interfaces - Haeb-Umbach, Reinhold; Beyerlein, Peter; Geller, Dieter (Philips Journal of Research)
Recognition accuracy has been the primary objective of most speech recognition research, and impressive results have been obtained, e.g. less than 0.3% word error rate on a speaker-independent digit recognition task. When it comes to real-world applications, robustness and real-time response might be more important issues. For the first requirement we review some of the work on robustness and discuss one specific technique, spectral normalization, in more detail. The requirement of real-time response has to be considered in the light of the limited hardware resources in voice control applications, which are due to the tight cost constraints. In this paper we discuss in detail one specific means to reduce the processing and memory demands: a clustering technique applied at various levels within the acoustic modelling.

Automatic Transcription of Unknown Words in a Speech Recognition System - Haeb-Umbach, Reinhold; Beyerlein, P.; Thelen, E. (ICASSP, Detroit)
We address the problem of automatically finding an acoustic representation (i.e. a transcription) of unknown words as a sequence of subword units, given a few sample utterances of the unknown words, and an inventory of speaker-independent subword units. The problem arises if a user wants to add his own vocabulary to a speaker-independent recognition system simply by speaking the words a few times. Two methods are investigated which are both based on a maximum-likelihood formulation of the problem. The experimental results show that both automatic transcription methods provide a good estimate of the acoustic models of unknown words. The recognition error rates obtained with such models in a speaker-independent recognition task are clearly better than those resulting from separate whole-word models. They are comparable with the performance of transcriptions drawn from a dictionary.

The Philips Research system for continuous-speech dictation - Steinbiss, Volker; Ney, Hermann J.; Aubert, Xavier L.; Besling, Stefan; Dugast, Christian; Essen, Ute; Geller, Dieter; Haeb-Umbach, Reinhold; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Tran, Bach Hiep (Philips Journal of Research)
This paper gives an overview of the Philips Research system for continuous-speech recognition. The recognition architecture is based on an integrated statistical approach. The system has been successfully applied to various tasks in American English and German, ranging from small vocabulary tasks to very large vocabulary tasks and from recognition only to speech understanding. Here, we concentrate on phoneme-based continuous-speech recognition for large vocabulary recognition as used for dictation, which covers a significant part of our research work on speech recognition. We describe this task and report on experimental results. In order to allow a comparison with the performance of other systems, a section with an evaluation on the standard North American Business news (NAB2) task (dictation of American English newspaper text) is supplied.

Continuous speech dictation - From theory to practice - Steinbiss, Volker; Ney, Hermann J.; Essen, Ute; Tran, Bach Hiep; Aubert, Xavier L.; Dugast, Christian; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Haeb-Umbach, Reinhold; Geller, Dieter; Hoellerbauer, W.; et al. (Speech Communication)
This paper gives an overview of the Philips research system for phoneme-based, large-vocabulary, continuousspeech recognition. The system has been successfully applied to various tasks in the German and (American) English languages, ranging from small vocabulary tasks to very large vocabulary tasks. Here, we concentrate on continuousspeech recognition for dictation in real applications, the dictation of legal reports and radiology reports in German. We describe this task and report on experimental results. We also describe a commercial PC-based dictation system which includes a PC implementation of our scientific recognition prototype. In order to allow for a comparison with the performance of other systems, a section with an evaluation on the standard Wall Street Journal task (dictation of American English newspaper text) is supplied. The recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. the Viterbi criterion is consistently applied both in training and testing; 2. continuous mixture densities are used without tying or smoothing; 3. time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon.

Synthesis Procedures for Self-Testable Controllers - Hellebrand, Sybille; Wunderlich, Hans-Joachim

Evaluation of Self-Testable Controller Architectures Based on Realistic Fault Analysis - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Goncalves, F.; Paulo Teixeira, Joao

Partitioning of CMOS-Circuits for On-Chip IDDQ-Testing - Hellebrand, Sybille; Herzog, Maik; Wunderlich, Hans-Joachim

Towards modelling of fuzzy functions - Hüllermeier, Eyke (in Proceedings EUFIT-95 3rd European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Rule-based modelling in fuzzy simulation - Hüllermeier, Eyke (in Proceedings ISFL-95 International Symposium on Logic, Zürich)

Fuzzy polynomial and spline interpolation - Hüllermeier, Eyke (in Proceedings IMACS Symposium on Systems Analysis and Simulation, Berlin)

Education for Visualization-Activities of the ACM-SIGGRAPH Education Committee - Domik-Kienegger, Gitta; Owen, GS (Proceedings of the Third Eurographics Workshop on Graphics and Visualization)

Die Gründung einer GmbH - Krimphove, Dieter; Brehmer, Carsten

Rechtliche Rahmenbedingungen des deutschen und internationalen Börsentermingeschäftes Ein Leitfaden für Banken, Sparkassen, Kreditinstitute, Anlagevermittler und Kunden mit Checklisten und Hinweisen zur Durchführung einer ordnungsgemäßen Anlageberatung - Krimphove, Dieter

Konjunkturzyklen aufgrund von Investitionsinterdependenzen: Simulation und empirische Überprüfung - Hüllermeier, Eyke (Moderne Makroökonomie-Eine kritische Bestandsaufnahme)

Rearrangement by intermediate ion/neutral complexes during the McLafferty fragmentation of unsaturated ketones - Dohmeier-Fischer, Silvia; Krämer, Nicolai; Grützmacher, Hans- Friedrich (European Journal of Mass Spectrometry)

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

A Distributed Computer Architecture for Qualitative Simulation based on a Multi-DSP and FPGAs - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Proceedings of the 3rd Euromicro Workshop on Parallel and Distributed Processing)

High-Performance Simulators Based on Multi-TMS320C40 - Brenner, Eugen; Ginthör-Kalcsics, Robert; Hranitzky, Robert; Platzner, Marco; Rinner, Bernhard; Steger, Christian; Weiss, Reinhold (Proceedings of the 5th Annual Texas Instruments TMS320 Educators Conference)

A Special-Purpose Coprocessor for Qualitative Simulation - Friedl, Gerald; Platzner, Marco; Rinner, Bernhard (Proceedings of the EURO-PAR'95 International Conference on Parallel Processing)

Parallel Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Proceedings of the EUROSIM Congress)

Improving Performance of the Qualitative Simulator QSIM - Design and Implementation of a Specialized Computer Architecture - Platzner, Marco; Rinner, Bernhard (Proceedings of the PDCS International Conference on Parallel and Distributed Computing Systems)

High-Performance Qualitative Simulation on a Multi-DSP Architecture - Platzner, Marco; Rinner, Bernhard (Proceedings of the 6th International Conference on Signal Processing Applications & Technology (ICSPAT))

Design and Implementation of Adaptive Digital Filters on a Multi-TMS320C40 System - Hranitzky, Robert; Platzner, Marco (Proceedings of the 6th International Conference on Signal Processing Applications & Technology (ICSPAT))

Hydrogen interaction with Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Groenen, J.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Optical properties of Sb-terminated GaAs and InP (110) surfaces - Santos, Paulo V.; Esser, N.; Cardona, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

III-V(110) surface dynamics from anab initiofrozen-phonon approach - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G. P. (Physical Review B)

Se/GaAs(110): energetics and structure - Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

Geometrical and electronic structure of the reconstructed diamond (100) surface - Kress, C.; Fiedler, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Exchange reactions versus adsorption geometries for Se/GaAs(110) - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Se/GaAs(110): Atomic and electronic structure - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Torque capability and control of a saturated induction motor over a wide range of flux weakening - Grotstollen, H.; Wiesing, J. (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Computer aided design and modeling of high frequency magnetic components - Becker, B.; Grotstollen, H.; Heinemann, L. (Proceedings of 1995 IEEE Applied Power Electronics Conference and Exposition - APEC'95)

Simulation of power electronic circuits with principles used in wave digital filters - Fiedler, A.; Grotstollen, H. (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of asymmetrical phase-shifted full bridge [power convertors] - Fiedler, A.; Grotstollen, H. (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Simulation model for ultrasonic motors powered by resonant converters - Maas, Jürgen; Ide, Peter; Fröhleke, Norbert; Grotstollen, Horst (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of PWM controlled, resonant transition converters with asymmetrical duty cycle - Fröhleke, Norbert; Fiedler, A.; Grotstollen, Horst; Margaritis, Basile (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Optimal pulsewidth modulation techniques for high-power voltage-source inverter - Sun, Jian

Hermann Ulrici (1806–1884). Der Hallesche Philosoph und die englische Algebra der Logik. Mit einer Auswahl von Texten Ulricis zur Logik und einer Bibliographie seiner Schriften - Peckhaus, Volker
Rezensionen: Philosophischer Literaturanzeiger 49 (1996), 325–328 (U. Dathe); Studia Logica 58 (1997), 335–337 (Roman Murawski); Modern Logic 8 (2000/01), 109–111 (H. Frank)

The Genesis of Grelling’s Paradox - Peckhaus, Volker (Logik und Mathematik. Frege-Kolloquium Jena 1993)
Abstract: Philosopher’s Index 30.2 (Sommer 1996), 215.

Hilberts Logik. Von der Axiomatik zur Beweistheorie - Peckhaus, Volker (NTM. Internationale Zeitschrift für Geschichte und Ethik der Naturwissenschaften, Technik und Medizin N.F.)
Rezension: Zbl. Math. 908.01010 (V.V. Pambuccian).

A Systematic Approach to State Feedback Controller Design for DC/DC Line-Side Traction Converters - Böcker, Joachim; Endrikat, Christian; Liu, Steven (EPE’95, Sevilla)

Netzkupplungsumrichter Jübek – Regelung - Janning, Jörg; Böcker, Joachim; Anbuhl, Kay; Boni, Marco (Elektrische Bahnen)

Grundprobleme der großen Philosophen. Philosophie der Neuzeit VI. Tarski, Reichenbach, Kraft, Gödel, Neurath. ed. Josef Speck, Vandenhoeck & Ruprecht: Göttingen 1992 (= Uni-Taschenbücher; 1654) - Peckhaus, Volker (Modern Logic)

“Russell y las ‘Paradojas’” [Rez. v. Alejandro R. Garciadiego, Bertrand Russell and the Origins of the Set-theoretic ‘Paradoxes’. Birkhäuser Verlag: Basel/Boston/Berlin 1992] - Peckhaus, Volker (Mathesis (México))

André Weil, Lehr- und Wanderjahre eines Mathematikers. aus dem Französischen von Theresia Übelhör, Birkhäuser Verlag: Basel/Boston/Berlin 1993 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)